2001
DOI: 10.1017/s0033291701004469
|View full text |Cite
|
Sign up to set email alerts
|

The Danish PET/depression project: PET findings in patients with major depression

Abstract: Our main finding is increased blood flow to the hippocampus, even when controlling for a number of confounders. This is in accordance with a rapidly expanding literature suggesting an important role for this structure in major depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 56 publications
5
57
1
2
Order By: Relevance
“…In fact, people with cerebellar lesions have displayed characteristics like passivity, blunting of emotion, and disinhibition of restraint similar to the depressed and manic states characteristic of mood disorders (Schmahmann and Sherman, 1998). Imaging studies suggest that a tonic increase in cerebellar activity is characteristic of major depression as determined by positron emission tomography (Videbech et al, 2001) and glucose utilization studies (Kimbrell et al, 2002). Accordingly, successful treatment of depression with venlafaxine has been associated with decreased blood flow to the cerebellum (Davies et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, people with cerebellar lesions have displayed characteristics like passivity, blunting of emotion, and disinhibition of restraint similar to the depressed and manic states characteristic of mood disorders (Schmahmann and Sherman, 1998). Imaging studies suggest that a tonic increase in cerebellar activity is characteristic of major depression as determined by positron emission tomography (Videbech et al, 2001) and glucose utilization studies (Kimbrell et al, 2002). Accordingly, successful treatment of depression with venlafaxine has been associated with decreased blood flow to the cerebellum (Davies et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Forty-six normal volunteers, mean age 41 AE 11X6 years (range 21±65 years, 16 males/30 females), participated in the study as part of a larger study dealing with affective disorders (Ravnkilde et al, 2001;Videbech et al, 2001aVidebech et al, , 2001bVidebech et al, , 2001c. The subjects were recruited by newspaper advertisement and had an average of 12X4 AE 2X4 years of education.…”
Section: Subjectsmentioning
confidence: 99%
“…All instructions and injections were given by the same two persons. Further details of imaging and statistical methods are described elsewhere (Videbech et al, 2001b).…”
Section: Imaging Proceduresmentioning
confidence: 99%
“…Sex differences in depressed populations, however, have not been the primary focus of clinical PET studies. Videbech et al (2001) reported significant sex differences in cerebral blood flow in the parietal lobe (and a trend for sex differences in the temporal lobe) for the entire sample of MDD patients and healthy controls (n ¼ 89, 42 patients including 12 males, 47 controls including 16 males). When regressing out the effects of sex and age, the research revealed increased blood flow to the hippocampus as the main finding in major depression, but no statistically significant correlations were found between any region and the Hamilton Depression Scale (HDS).…”
Section: Evidence For Sex Differencesmentioning
confidence: 96%